Inheritance [compact disc, unabridged] - Paolini, Christopher (Paolini, Christopher. Inheritance, 2011)
Eragon Dragon Rider and Saphira have come further than anyone dared to hope in ridding their land of tyranny. But can they topple the evil king Galbatorix and restore justice to Alagaësia? And if so, at what cost?